Tail risk transmission: A study of the Iran food industry - Fatemeh Mojtahedi; Seyed Mojtaba Mojaverian; Daniel Felix Ahelegbey; Paolo Giudici (Risks, 2020)
This paper extends the extreme downside correlation (EDC) and extreme downside hedge (EDH) methodology to model the interdependence in the sensitivity of assets to the downside risk of other financial assets under severe firm-level and market conditions. The model is applied to analyze both systematic and systemic exposures in the Iranian Food Industry. The empirical application investigates (1) which company is the safest for investors to diversify their investment, and (2) which companies are the "transmitters" and "receivers" of downside risk. We study the return series of 11 companies and the Food Industry index publicly listed on the Tehran Stock Exchange. The data covers daily close prices from 2015-2020. The result shows that Mahram Manufacturing is the safest to hedge equity risk, and Glucosan and Behshahr Industries are the riskiest, while Gorji Biscuit is central to risk transmission, and Pegah Fars Diary is the main "receiver" of risk in turbulent times.
Keywords: C31; C58; G01; G12; 330; food industry; extreme downside hedge; extreme downside correlation; systematic risk; systemic risk